Acute renal failure following copper sulphate intoxication. - Chugh, K. S. (BMJ Group, 1977)
Eleven out of a series of twenty-nine patients (37-9%) with acute copper sulphate poisoning developed acute renal failure. Intravascular haemolysis appeared to be the chief factor responsible for renal lesions in these patients. Histological lesions observed in the kidney varied from those of mild shock to well established acute tubular necrosis. In one case, granulomatous lesions were seen in response to tubulorrhexis. Renal failure was the chief indication for dialysis in ten patients, whereas one patient was dialysed primarily for removal of copper. Notwithstanding the adequate control of uraemia by dialysis, only six of the eleven patients recovered. Septicaemia was responsible for death in three, hepatic failure in one and methaemoglobinaemia in another. It is postulated that release of copper from haemolysed red cells during acute haemolytic episodes may initiate, or contribute to, the development of renal damage.